2011
DOI: 10.2967/jnumed.110.081208
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Mineral Deposition in Carotid Plaque Using 18F-Sodium Fluoride PET/CT: Correlation with Atherogenic Risk Factors

Abstract: The purpose of this study was to correlate 18 F-sodium fluoride accumulation in the common carotid arteries of neurologically asymptomatic patients with cardiovascular risk factors and carotid calcified plaque burden. Methods: Two hundred sixtynine oncologic patients were examined by 18 F-sodium fluoride PET/CT. Tracer accumulation in the common carotid arteries was analyzed both qualitatively and semiquantitatively by measuring the blood-pool-corrected standardized uptake value (target-to-background ratio) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
111
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 32 publications
(66 reference statements)
3
111
0
Order By: Relevance
“…Several other studies have reported similar findings and have led to growing support for the use of 18 F‐NaF for imaging the process of microcalcification and visualizing ongoing mineral deposition within the atherosclerotic plaque 64, 99, 100, 101, 102, 103…”
Section: Positron Emission Tomographymentioning
confidence: 64%
See 4 more Smart Citations
“…Several other studies have reported similar findings and have led to growing support for the use of 18 F‐NaF for imaging the process of microcalcification and visualizing ongoing mineral deposition within the atherosclerotic plaque 64, 99, 100, 101, 102, 103…”
Section: Positron Emission Tomographymentioning
confidence: 64%
“…Ten‐year Framingham risk scores for CVD and death are related to 18 F‐NaF uptake 64. Other retrospective studies have shown positive correlations between arterial 18 F‐NaF uptake and CVD risk factors, including age, sex, hypertension, hypercholesterolemia, and diabetes mellitus, further supporting the notion that 18 F‐NaF PET imaging may improve CVD risk stratification 98, 100, 101, 102, 104, 111, 112, 113, 114…”
Section: Positron Emission Tomographymentioning
confidence: 81%
See 3 more Smart Citations